The position of authentic literature in primary ELT in Croatia - Ivana Cindrić; Silvija Hanžić Deda; Ivana Milković (ExELL (Explorations in English Language and Linguistics))
This study explores Croatian primary teachers’ use of authentic literature in English language teaching (ELT). It examines teachers’ perceptions and practices, including differences based on teachers’ initial education and age. The findings reveal that teachers, regardless of initial education and age, use stories in their classes, typically once or twice a month. The main source of authentic literary texts for these teachers is the coursebook. There were no significant differences observed in terms of frequency and type of text used based on teachers’ age. Overall, teachers have positive attitudes towards using authentic literature, although they express concerns about the increased teacher engagement required for preparation and delivery, as well as the time constraints of English lessons.